Hypothetical learning trajectory sistem pertidaksamaan linear dua variabel berbasis etnomatematika untuk mendukung pengembangan kemampuan penalaran matematika siswa SMK - Fadhilah Fadhilah; Ardian Saputra; Herlina Maya Sari; Herda Yowan Mei Randa; Nila Kesumawati; Allen Marga Retta (IKIP Siliwangi, 2026)
This study was motivated by the low mathematical reasoning ability of vocational high school students. This study aimed to design an ethnomathematics-based Hypothetical Learning Trajectory on the topic of SPtLDV employed Didactical Design Research at the prospective analysis stage through data collection in the form of textbook and learning material analysis, diagnostic tests involving 14 students, interviews, and documentation. The data were analyzed through data reduction, data presentation, and conclusion. The results showed the existence of epistemological, ontogenical, and didactical obstacles in learning SPtLDV. Based on these obstacles, an HLT was designed consisting of activities involving identifying contextual problems, mathematical modeling, graphical representation, and drawing conclusions by integrating local cultural contexts. The novelty of this study lies in the development of an ethnomathematics-based HLT grounded in the identification of students’ learning obstacles and the integration of local cultural contexts.